2011
DOI: 10.1111/j.1552-3934.2010.02065.x
|View full text |Cite
|
Sign up to set email alerts
|

An After-School Program on Nutrition and Physical Activity for Elementary School Children

Abstract: This study describes the Food and Fitness Fun Education Program (FFFEP), which was implemented in an after‐school child care program in California. FFFEP consisted of 16 weeks of lessons and activities. Changes in healthy eating and physical activity in children and their parents were analyzed using pre‐ and posttests for children and a parent survey. In all, 1,810 children in kindergarten through fifth grades participated in the program. Testing of the children took place at the beginning and end of the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…Evidence has indicated that lifestyle diseases may develop during early childhood 6–9 . Physical inactivity and poor nutrition in childhood has been shown to adversely correlate with chronic lifestyle diseases, including obesity, cardio‐metabolic health and mental health outcomes 10–12 . Physical activity and diet appear as two significant modifiable risk factors with the potential to reduce the current health inequalities 13,14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has indicated that lifestyle diseases may develop during early childhood 6–9 . Physical inactivity and poor nutrition in childhood has been shown to adversely correlate with chronic lifestyle diseases, including obesity, cardio‐metabolic health and mental health outcomes 10–12 . Physical activity and diet appear as two significant modifiable risk factors with the potential to reduce the current health inequalities 13,14 .…”
mentioning
confidence: 99%
“…[6][7][8][9] Physical inactivity and poor nutrition in childhood has been shown to adversely correlate with chronic lifestyle diseases, including obesity, cardio-metabolic health and mental health outcomes. [10][11][12] Physical activity and diet appear as two significant modifiable risk factors with the potential to reduce the current health inequalities. 13,14 A lack of cultural understanding has emerged as a potential barrier limiting Australian Indigenous communities from engaging in health intervention and strategies.…”
mentioning
confidence: 99%
“…Communications was utilized in an intervention to help children learned aspects of media campaigning, in which they developed refrigerator magnets, a web site, a commercial, and a rap song to promote healthy behaviors for among their family members [ 22 ]. Other innovative programs included teaching various aspects of theater production, which culminated with a play performances at the school [ 32 ], and teaching children agriculture through developing and maintaining a community gardening [ 40 ]. From these examples it is clear that the opportunities in the after school environment are vast.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity measurements mainly relied on self-report, as four studies utilized brief surveys [ 18 , 19 , 20 , 21 , 22 ], three utilized physical activity recalls [ 23 , 25 , 26 ], and three [ 35 , 38 , 39 ] used accelerometry. One study also used parents to recall the amount of physical activity their child(ren) participated in over a period of time [ 40 ]. Diet was similar as six studies relied on self-report [ 21 , 23 , 30 , 33 , 36 , 38 , 39 , 41 ], and three relied on parent recalls [ 29 , 34 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation